Correction: Single-molecule nanopore sensing of actin dynamics and drug binding. Issue 30 (23rd July 2020) - Wang, Xiaoyi; Wilkinson, Mark D.; Lin, Xiaoyan; Ren, Ren; Willison, Keith R.; Ivanov, Aleksandar P.; Baum, Jake; Edel, Joshua B.
Abstract : Correction for 'Single-molecule nanopore sensing of actin dynamics and drug binding' by Xiaoyi Wang et al., Chem. Sci., 2020, 11, 970–979, DOI: ; 10.1039/C9SC05710B .